STUDENTS’PERSPECTIVES ON THE USE OF BLENDED LEARNING DURING THE COVID-19 PANDEMIC - Enni Erawati Saragih; Muhamad Rizky Bahtiar (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2022)
The COVID-19 pandemic is affecting all countries, including Indonesia, which has restricted all outside activities. It is also prominent in the field of education, where blended learning is used in the learning process, resulting in a variety of views for students. The researcher wanted to know the students’ point of view of this method. The aims of the research are to describe students' perspectives on the use of blended learning in learning activities during the COVID-19 pandemic. Blended learning is a combination of face-to-face and online instruction. This study used a qualitative research design, with questionnaires and interviews as data collection. The participants of the study were 14 second-year university students who used blended learning activities. The results of the study show the effectiveness, benefits, constraints, and effects of blended learning on students' perspectives during COVID-19.